Health Information Systems: Current Challenges and Developments - Bréant, C.; Managing Editor for the IMIA Yearbook Section on Health Information Systems (Yearbook of Medical Informatics, 2008)
Objectives To summarize excellent current research in the field of Health Information Systems.Method Synopsis of the articles selected for the IMIA Yearbook 2008.Results HIS is a broad field that includes many fruitful areas of research and development. Some current topics were selected for this IMIA yearbook.Conclusions The best paper selection of articles on health information systems shows examples of original developments in the area of: medical record systems to meet specific requirements in a developing country, methodologies to identify strengths and weaknesses of hospital information systems, networking of hospital information systems towards an integrated regional health platform, and development of an open source picture archiving and communication systems to facilitate the integration of advanced new imaging functionalities.
Keywords: Medical informatics; International Medical Informatics Association; health information systems